2006
DOI: 10.1158/1078-0432.ccr-06-1475
|View full text |Cite
|
Sign up to set email alerts
|

Fragile Histidine Triad Expression in Oral Squamous Cell Carcinoma and Precursor Lesions

Abstract: Pupose: Fragile histidine triad (FHIT) expression in precursor oral lesions (POL) and oral squamous cell carcinomas (OSCC) was studied with regard to (a) the frequency of loss of FHIT expression, (b) whether loss of FHITexpression correlates with degree of dysplasia in POLs, (c) whether FHIT loss predicts high-risk POLs that are more likely to transform, and (d) whether FHIT loss in OSCCs correlates with survival. Experimental Design: Ninety-four POLs and 86 OSCCs were immunostained for FHIT. Survival analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 42 publications
0
15
1
Order By: Relevance
“…Characterization of the pattern of human FHIT expression could contribute to our understanding of the function of this protein in normal tissues and provide a reference framework for interpretation of abnormal FHIT expression in human tumors. In contrast to previously published studies that reported exclusively cytoplasmic localization of FHIT, we showed a nuclear and cytoplasmic localization of the FHIT protein by immunohistochemical methods [12]. We, therefore, aim to perform a comprehensive immunohistochemical analysis of FHIT expression in normal human tissues and compare FHIT expression with proliferation and diff erentiation within individual organs.…”
Section: Introductioncontrasting
confidence: 60%
See 3 more Smart Citations
“…Characterization of the pattern of human FHIT expression could contribute to our understanding of the function of this protein in normal tissues and provide a reference framework for interpretation of abnormal FHIT expression in human tumors. In contrast to previously published studies that reported exclusively cytoplasmic localization of FHIT, we showed a nuclear and cytoplasmic localization of the FHIT protein by immunohistochemical methods [12]. We, therefore, aim to perform a comprehensive immunohistochemical analysis of FHIT expression in normal human tissues and compare FHIT expression with proliferation and diff erentiation within individual organs.…”
Section: Introductioncontrasting
confidence: 60%
“…For scoring, negative and low (no staining or immunoreactivity staining present in <10% of cells) staining scores and moderate (immunoreactivity in ≥10-50% of cells) and strong (immunoreactivity in >50% of cells) staining scores were combined as negative or positive, respectively, as described previously by Kujan et al [12]. The software SPSS 22.0 was used to analyze all the statistical analyses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Few studies have identified FHIT to be a predictor of poor survival in OSCC [34] in HNSCC [35]. However, these studies did not analyze the status of p53 aberrations in the tumors.…”
Section: Discussionmentioning
confidence: 99%